MMP-13 is constitutively produced in human chondrocytes and co-endocytosed with ADAMTS-5 and TIMP-3 by the endocytic receptor LRP1 - Yamamoto, K; Okano, H; Miyagawa, W; Visse, R; Shitomi, Y; Santamaria, S; Dudhia, J; Troeberg, L; Strickland, D; Hirohata, S; Nagase, H (Elsevier, 2016)
Matrix metalloproteinase 13 (MMP-13) degrades collagenous extracellular matrix and its aberrant activity associates with diseases such as arthritis, cancer, atherosclerosis and fibrosis. The wide range of MMP-13 proteolytic capacity suggests that it is a powerful, potentially destructive proteinase and thus it has been believed that MMP-13 is not produced in most adult human tissues in the steady state. Present study has revealed that human chondrocytes isolated from healthy adults constitutively express and secrete MMP-13, but that it is rapidly endocytosed and degraded by chondrocytes. Both pro- and activated MMP-13 bind to clusters II and III of low-density lipoprotein (LDL) receptor-related protein 1 (LRP1). Domain deletion studies indicated that the hemopexin domain is responsible for this interaction. Binding competition between MMP-13 and ADAMTS-4, -5 or TIMP-3, which also bind to cluster II, further shown that the MMP-13 binding site within cluster II is different from those of ADAMTS-4, -5 or TIMP-3. MMP-13 is therefore co-endocytosed with ADAMTS-5 and TIMP-3 by human chondrocytes. These findings indicate that MMP-13 may play a role on physiological turnover of cartilage extracellular matrix and that LRP1 is a key modulator of extracellular levels of MMP-13 and its internalization is independent of the levels of ADAMTS-4, -5 and TIMP-3.